Cultural Distortion in Marriage Taaruf Through Matchmaking Applications from the Perspective of Islamic Law - Muhammad Saleh; Nurlaila Harun; Eti Yusnita; Hendriyanto Hendriyanto; Sheyra Silvia Siregar (Faculty of Law, Universitas Pekalongan, 2025)
The advancement of technology has transformed the way individuals seek life partners, including among Muslims. One emerging phenomenon is the use of matchmaking applications as a medium for taaruf in preparation for marriage. This study aims to analyze the use of matchmaking applications as a taaruf medium from the perspective of Islamic law. The research employs a qualitative method with a literature study approach, examining various sources related to Islamic family law, the concept of taaruf, and the use of technology in partner-seeking. The findings indicate that Islam does not prohibit the use of technology in finding a spouse, provided that Sharia principles are upheld, such as maintaining interaction boundaries, involving a guardian (wali), and prioritizing the right intentions. Several applications offer features that support Islamic taaruf, such as identity verification, filtering potential partners based on Islamic values, and guardian supervision in communication. However, challenges such as the risk of identity misuse and potential deviations from Islamic norms must be considered. Therefore, regulations and user education are necessary to ensure that these applications are used wisely and remain within the framework of Islamic law. With the right approach, matchmaking applications can serve as a modern solution for realizing Islamic marriages characterized by sakinah, mawaddah, and rahmah.